2011
DOI: 10.1016/j.socscimed.2011.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how race/ethnicity and gender define age-trajectories of disability: An intersectionality approach

Abstract: A number of studies have demonstrated wide disparities in health among racial/ethnic groups and by gender, yet few have examined how race/ethnicity and gender intersect or combine to affect the health of older adults. The tendency of prior research to treat race/ethnicity and gender separately has potentially obscured important differences in how health is produced and maintained, undermining efforts to eliminate health disparities. The current study extends previous research by taking an intersectionality app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
275
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(300 citation statements)
references
References 72 publications
(206 reference statements)
10
275
1
3
Order By: Relevance
“…that must be analyzed together, given their interrelations, which influence disparities and create vulnerabilities to health risks. The higher obesity among diabetic black elderly women found in our study may have been influenced by unfavorable conditions faced by this group over their lives 15,47 , even in cases in which they reached higher levels of schooling 17 , due to reduced opportunities for upward social mobility, in addition to differences and worse care in health services, a reflex of racial discrimination and social exclusion 20,47 . Cunningham et al 48 showed that, over an eight year period, there was a significant increase in WC and BMI among black women who reported greater racial discrimination (the same was not found for black and white men or for white women).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…that must be analyzed together, given their interrelations, which influence disparities and create vulnerabilities to health risks. The higher obesity among diabetic black elderly women found in our study may have been influenced by unfavorable conditions faced by this group over their lives 15,47 , even in cases in which they reached higher levels of schooling 17 , due to reduced opportunities for upward social mobility, in addition to differences and worse care in health services, a reflex of racial discrimination and social exclusion 20,47 . Cunningham et al 48 showed that, over an eight year period, there was a significant increase in WC and BMI among black women who reported greater racial discrimination (the same was not found for black and white men or for white women).…”
Section: Discussionmentioning
confidence: 71%
“…Racial differences associated with higher morbity 19,46,47 , obesity 9,15,22,29 and disability 16,28 are largely explained by unfavorable socioeconomic conditions, with lead to an accumulation of unhealthy behaviors and lifestyle, due to lower access to information, quality education and health services. According to Chor 20 , race, socioeconomic status and gender are crucial variables Table 4 Effect of race on body fat among diabetic elderly individuals according to gender, adjusted by schooling and family income.…”
Section: Discussionmentioning
confidence: 99%
“…Again, bereavement is a known risk factor for mental and physical health (20), and childhood through early adulthood may be a period of the life course during which bereavement is especially likely to have lasting consequences (14)(15)(16)(17)(18). Although the United States has made progress in recent decades in reducing the life expectancy gap between blacks and whites, significant racial differences persist (5, 6), with important implications for surviving family members.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,[12][13][14][37][38][39][40] Socioeconomic factors (e.g., poverty and education) have been shown to be associated with prevalent functional disability but not HAD. 11,12 The distribution of HAD suggests that there may also be different factors contributing to susceptibility for or poor recovery from HAD within each age group.…”
Section: Discussionmentioning
confidence: 99%